Acupuncture for treating diabetic retinopathy: A systematic review and meta-analysis of randomized controlled trials. (August 2020) - Ang, Lin; Song, Eunhye; Jun, Ji Hee; Choi, Tae-Young; Lee, Myeong Soo
Highlights: Diabetic retinopathy (DR) is one of the most common microvascular diabetes complications. The combined therapy of acupuncture with standard medicine or acupuncture alone may increase the total effective rate and improve visual acuity. The promising findings were inconclusive as the methodological quality of the included studies was concerning. RCTs with high methodological and reporting qualities are indispensable in the future. Abstract: Objective: This review aimed to examine the effectiveness of acupuncture for the treatment of diabetic retinopathy (DR). Methods: Fourteen databases (5 English, 4 Chinese, and 5 Korean) were searched from their inception until May 20, 2020. Randomized controlled trials (RCTs) using acupuncture for DR treatment were included. The study selection and data extraction were performed by two independent reviewers. The Cochrane risk of bias tool version 2 (RoB 2.0) and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) were used to assess all the included RCTs. Results: Of 864 citations, 6 RCTs met the inclusion criteria of our review. Four studies reported the beneficial effects of acupuncture with standard medication or acupuncture alone compared with standard medication or no treatment on the effective rate. Only three studies showed that acupuncture combined with standard medications significantly improved visual acuity compared to standard medication alone. None of the studies reported on adverse events. The risk of bias of the included studies was judged to be of "some concern" and was marked with a moderate and low certainty of evidence in different outcomes. Conclusion: Our results suggest the potential benefit of acupuncture in treating DR. Acupuncture in the form of combined therapy with standard medication or acupuncture alone may be more effective in the treatment of DR than standard medication alone. Further rigorous clinical trials are needed to confirm these findings.